Strategi Pembelajaran Sejarah Berbasis Sumber Primer sebagai Upaya Menumbuhkan Sikap Kritis Peserta Didik - Nadia Rahmawati; Allyah Zahirah; Radit Septa Wijaya; Syarifuddin Syarifuddin; Rani Oktapiani (Indo Publishing, 2026)
History learning has an important role in developing students’ critical thinking skills through understanding past events. However, in practice, history learning often still relies on lecture methods and memorization, which limits students’ opportunities to analyze and interpret historical events critically. This study aims to examine the implementation of a history learning strategy based on primary sources as an effort to foster students’ critical attitudes. This research uses a qualitative approach with a descriptive method. The research subjects consist of history teachers and senior high school students. Data were collected through observation, interviews, and documentation. The results of the study show that the use of primary sources such as historical documents, archives, photographs, and manuscripts can increase students’ engagement in the learning process. Students become more active in observing, analyzing, interpreting, and drawing conclusions from historical information obtained from these sources. In addition, primary source-based learning strategies encourage students to ask questions, express opinions, and compare different perspectives on historical events. Thus, the implementation of primary source-based history learning strategies can be an effective alternative in developing students’ critical attitudes in history learning